Allele-specific expression in the human heart and its application to postoperative atrial fibrillation and myocardial ischemia. Issue 1 (December 2016) - Sigurdsson, Martin; Saddic, Louis; Heydarpour, Mahyar; Chang, Tzuu-Wang; Shekar, Prem; Aranki, Sary; Couper, Gregory; Shernan, Stanton; Seidman, Jon; Body, Simon; Muehlschlegel, Jochen
Abstract Background Allele-specific expression (ASE) is differential expression of each of the two chromosomal alleles of an autosomal gene. We assessed ASE patterns in the human left atrium (LA, n = 62) and paired samples from the left ventricle (LV, n = 76) before and after ischemia, and tested the utility of differential ASE to identify genes associated with postoperative atrial fibrillation (poAF) and myocardial ischemia. Methods Following genotyping from whole blood and whole-genome sequencing of LA and LV samples, we called ASE using sequences overlapping heterozygous SNPs using rigorous quality control to minimize false ASE calling. ASE patterns were compared between cardiac chambers and with a validation cohort from cadaveric tissue. ASE patterns in the LA were compared between patients who had poAF and those who did not. Changes in ASE in the LV were compared between paired baseline and post-ischemia samples. Results ASE was found for 3404 (5.1%) and 8642 (4.0%) of SNPs analyzed in the LA and LV, respectively. Out of 6157 SNPs with ASE analyzed in both chambers, 2078 had evidence of ASE in both LA and LV (p < 0.0001). The SNP with the greatest ASE difference in the LA of patients with and without postoperative atrial fibrillation was within the gelsolin (GSN ) gene, previously associated with atrial fibrillation in mice. The genes with differential ASE in poAF were enriched for myocardial structure genes, indicating the importance of atrial remodeling in the pathophysiology of AF. The greatest change in ASE between paired post-ischemic and baseline samples of the LV was in the zinc finger and homeodomain protein 2 (ZHX2 ) gene, a modulator of plasma lipids. Genes with differential ASE in ischemia were enriched in the ubiquitin ligase complex pathway associated with the ischemia-reperfusion response. Conclusions Our results establish a pattern of ASE in the human heart, with a high degree of shared ASE between cardiac chambers as well as chamber-specific ASE. Furthermore, ASE analysis can be used to identify novel genes associated with (poAF) and myocardial ischemia.